High Rate Navigation, State Parameter, and Microphysics Flight-Level Data [NCAR/EOL] - NCAR/EOL Research Aviation Facility (Arctic Data Center)
This data set includes airborne measurements obtained from the NCAR Research Aviation Facility (RAF) C-130 aircraft (Tail Number: N130AR) during the Southern Great Plains 1999 Hydrology Experiment (SGP99) project. This dataset contains high rate navigation, state parameter, and microphysics flight-level data in NetCDF format.